2007
DOI: 10.1007/s00595-006-3351-1
|View full text |Cite
|
Sign up to set email alerts
|

Successful Resection of Hepatocellular Carcinoma with Bronchobiliary Fistula Caused by Repeated Transcatheter Arterial Embolizations: Report of a Case

Abstract: Bronchobiliary fistula (BBF) is a rare but life-threatening condition. We herein describe a rescued case of a patient with hepatocellular carcinoma (HCC) who developed BBF as a late complication of transcatheter arterial embolization (TAE). A 66-year-old man underwent repeated TAE for a large HCC during a 3-year period. Massive biliptysis developed after the last treatment and bronchoscopy proved the presence of BBF. Radiological studies exhibited a necrotic HCC in the right liver with a tumor thrombus protrud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In terms of diagnosis, CT imaging is usually the predominant modality or biliary scintigraphy with hepatic iminoacetic acid (HIDA) which demonstrates initial tracer activity in the liver which migrates into the chest cavity (12). BBF can also be diagnosed by interventional techniques, such as ERCP, percutaneous transhepatic cholangiography, bronchoscopy or fistulography (4,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of diagnosis, CT imaging is usually the predominant modality or biliary scintigraphy with hepatic iminoacetic acid (HIDA) which demonstrates initial tracer activity in the liver which migrates into the chest cavity (12). BBF can also be diagnosed by interventional techniques, such as ERCP, percutaneous transhepatic cholangiography, bronchoscopy or fistulography (4,13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of a BBF is generally considered to include the following: the mechanical effects of increased intraluminal pressure on the biliary system due to obstruction of the bile duct and the presence of local inflammatory or infectious processes, such as a subphrenic or liver abscess [14, 15]. Clinically, the presence of bilioptysis is a pathognomonic sign of BBF [16, 17], and a definitive diagnosis can be made by ERC, bronchoscopy, or percutaneous transhepatic cholangiography [6, 14, 18]. Bilioptysis led us to suspect a BBF in our patient because it has been reported that bilioptysis is seen in all BBF patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, surgery for BBF in a patient, who has undergone liver resections and who is in a state of sepsis, could add to the negative sentiments for retrieval. 3 , 7 Nonsurgical treatments such as radiological and endoscopic interventions, which are less riskier than surgery, have been recently highlighted. In the previous cases, patients with BBF following RFA which are complicated by biloma or liver abscess successfully underwent external drainages with or without endoscopic drainage.…”
Section: Discussionmentioning
confidence: 99%